1987
DOI: 10.1161/01.res.60.5.674
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of myocardial diastolic function using three-dimensional echocardiographic reconstructions: application of a new method for study of acute ischemia in dogs.

Abstract: The effect of acute myocardial ischemia on the myocardial elastic modulus has been a matter of controversy. To evaluate this question, diastolic elastic modulus was assessed by finite element analysis of left ventricular geometry using three-dimensional echocardiographic reconstructions and right and left ventricular pressure recordings. Elastic properties were estimated before and after coronary occlusion in 6 open-chest dogs. Elastic modulus values were derived by means of a computer program that determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Nevertheless, approaches to assessing myocardial material properties during systole are essential to an improved understanding of the relationship between contractility and myocardial morphologic features. McPherson et al 44 have used the finite element approach to assess diastolic elastic modulus by determining the global elastic modulus that best predicted diastolic deformations in ventricular geometry after coronary occlusion. It is conceivable that this approach might be used in a systolic model.…”
Section: Limitations Of This Studymentioning
confidence: 99%
“…Nevertheless, approaches to assessing myocardial material properties during systole are essential to an improved understanding of the relationship between contractility and myocardial morphologic features. McPherson et al 44 have used the finite element approach to assess diastolic elastic modulus by determining the global elastic modulus that best predicted diastolic deformations in ventricular geometry after coronary occlusion. It is conceivable that this approach might be used in a systolic model.…”
Section: Limitations Of This Studymentioning
confidence: 99%
“…Left ventricular shortening has been measured along various axes in canine hearts using a number of measurement techniques. 10 - 33 To date, however, the anisotropy of left ventricular shortening in human hearts has not been reported, although the relative dynamics of specific left ventricular 916 Circulation Research Vol 64, No 5, May 1989 sites (as required for the measurement of such shortening) have been studied in man both during and after cardiac surgery by means of radiopaque clips attached to the epicardium, 34 -36 strain gauges sutured to the epicardium, 37 opacified coronary artery bifurcations, 3839 radiopaque myocardial markers implanted into the midwall 40 and sonomicrometers implanted at various transmural depths. 4142 We report here the results of a study investigating the anisotropy of systolic shortening in the inferior, anterior, lateral, and septal regions of the left ventricular midwall of the transplanted heart in awake man.…”
mentioning
confidence: 99%
“…Many researchers reported that diastolic regional stiffness of the ischemic myocardium increased (Hess et al 1980;McPherson et al 1987;Sys and Brutsaert 1989;Ross 1989). Edwards et al suggested that a sevenfold increase in passive loading would be sufficient to produce the acute elongation of the ischemic myocardium (Edwards et al 1981), which is roughly consistent with the result in this study.…”
Section: The Mesh Structure Of the Modelmentioning
confidence: 99%